Where the creek bends ebook - Miller, Linda Lael (2024)
From acclaimed #1 New York Times bestselling author Linda Lael Miller comes a beautifully rendered timeslip novel about the family we create for ourselves... Madison Bettencourt has tried to assemble all the pieces of a perfect life, but nothing fits quite the way it should. She's moved back home to Montana to care for her grandmother, who is slipping further and further away. And she's called off her wedding, and worries her dreams of a family are fading with it. As Madison rattles around her family home, childhood memories come flooding back. Bliss Morgan transformed eight-year-old Madison with her loyalty, and for a while, the two girls were as close as can be. But Madison never understood why Bliss suddenly vanished, leaving only a friendship bracelet and a message etched into a matchbook. Before she can begin again, Madison must uncover what happened to Bliss, and Liam McKettrick—a widowed dad trying to repair his relationship with his two children—becomes her unlikely ally. He, too, understands the pang of regret. Yet there are mysteries that Madison hesitates to explore with anyone, and strange energies in Bettencourt Hall that blur the lines between past and present. Poignant and utterly captivating, Where the Creek Bends shows that finding yourself begins with following your heart, no matter where it leads. Perfect for fans of: Second Chances Family Drama Small Town settings Susan Mallery, Nicolas Sparks and Ashley Poston